Utopia Islam Disfungsi Subliminal Message dalam Media Sosial - Ahmad Tamrin Sikumbang; Zainun Zainun; Imam El Islamy (JURNAL SIMBOLIKA: Research and Learning in Communication Study (E-Journal), 2020)
This study aims to see how subliminal dysfunction occurs in social media in an Islamic context. The research technique used is literature study, looking at various sources regarding subliminals and relating them to conditions in social media. This type of research is descriptive qualitative research, which is a research process to understand human or social problems by creating a comprehensive and complex picture presented in words, reporting detailed views obtained from information sources, and carried out in a different setting natural. While the approach used is phenomenology, which is to describe the reality that is happening without explaining the relationship between variables. The research results obtained are that Islam teaches its people to have ethics in carrying out all activities, including communication on social media. In the concept of Subliminal Message from hidden messages invites the public to never trust the information received from social media, before finding out the truth and accuracy of the message, from sources that can be trusted, supported, and related to the message. The conclusion in this research is that the Subliminal Message concept invites the public to never believe the information received from social media, before finding out the truth and accuracy of the message, from sources that can be trusted, supported, and related to the message.